The Thistle and the Drone : How America's War on Terror Became a Global War on Tribal Islam - Ahmed, Akbar S. (Book collections on Project MUSE., 2013)
Argues that the campaigns that fall under "The War on Terror" have exacerbated the already-broken relationship between central Islamic governments and the tribal societies within their borders.